Pro SharePoint 2010 search - Noble, Josh 1977- (Apress, 2011)
Pro SharePoint 2010 Search gives you expert advice on planning, deploying and customizing searches in SharePoint 2010. Drawing on the authors? extensive experience of working with real-world SharePoint deployments, this book teaches everything you'll need to know to create well-designed SharePoint solutions that always keep the end-user?s experience in mind. Increase your search efficiency with SharePoint 2010?s search functionality: extend the search user interface using third-party tools, and utilize analytics to improve relevancy. This practical hands-on book is a must-have resource for anyone looking to unlock the full potential of their SharePoint server's search capabilities. Pro SharePoint 2010 Search empowers you to customize a SharePoint 2010 search deployment and maximize the platform?s potential for your organization.